The Role of the PNM Mekaar Syariah Program in Empowering Micro Enterprises: A Case Study in Nagari Cubadak, Pasaman Regency - Audia, Annisa; Dewi, Yenti Astarie (The Future of Education Journal, 2025)
The aim of this research is to find out the role of PNM Mekaar Syariah in developing micro businesses and how to utilize the business capital provided by PNM Mekaar Syariah for customers. This research uses a qualitative descriptive method, the objectives and data sources used are primary data and secondary data, the data collection techniques used are interviews and documentation. Based on the results of the research conducted, it can be seen that PNM Mekaar Syariah has a role in developing customers' micro businesses. Because, with the capital financing provided by PNM Mekaar Syariah, it can help customers in running their businesses. Apart from that, PNM also plays a role in providing assistance and business training to customers while running their business. However, this assistance did not work effectively because many customers were unable to attend the weekly meeting. The meeting aims to nail down the payment of weekly financing installments as well as mentoring and training. This lack of assistance has led to misuse of capital for some customers. However, most customers have made good use of this capital to run their businesses.